PENGARUH JUS BUAH DURIAN (Durio zibethinus Murr.) TERHADAP PROFIL FARMAKOKINETIK PARASETAMOL PADA TIKUS PUTIH (Rattus norvegicus L.) JANTAN GALUR WISTAR - ., Pinondang Ruth Paber Simaremare (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2013)
Paracetamol is widely used as analgesic and antipyretic agent in treatment of painand fever. Paracetamol has interaction with carbohydrates and alcohol. Durian is the fruitnative of Indonesia, that contain carbohydrates and alcohol. The aims of this researchwere to study the influence of durian fruit juice to the absorption and elimination kineticsof paracetamol and to know the dose of durian fruit juice that influence the absorptionand elimination kinetics of paracetamol. The study was conducted using 16 rats, dividedinto 4 groups (n=4 per group). Each group was treated the following treatment : controlparacetamol (paracetamol 9 mg/200 gBW), dose 1 group (paracetamol 9 mg/200 gBWand 0.675 g/200 gBW of durian fruit juice), dose 2 group (paracetamol 9 mg/200 gBWand 1.350 g/200 gBW of durian fruit juice) and dose 3 group (paracetamol 9 mg/200gBW and 2.700 g/200 gBW of durian fruit juice). Blood sampling is done from the veinof rats tail at minutes 10, 20, 30, 40, 60, 90, 120, 180, 240, 300 and 360. The quantitationof paracetamol in plasma was determined by UV spectrophotometer at 243 nm. Resultshowed that durian fruit juice changed the absorption kinetics of paracetamol, durianfruit juice decreased Ka,